A Studi Kasus: Analisis Laju Korosi Terhadap Berbagai Jenis Paku - Hakim, Muh. Supwatul; Hermayantiningsih, Dwi; Nainggolan, Yuni; Sugiyani, Tina; Simbolon, Wenika; Yuneta; Silalahi, Anasthasya (LPPM Sekolah Tinggi Teknologi Cipasung, 2024)
Abstract— This research aims to determine the corrosion rate of different types of nails by immersing them in water of the same quality. The method used is weight loss method. Each nail was immersed in water for 1–7 days and then weighed every day. The highest corrosion rate was obtained for steel nails with an average corrosion rate of 0.09 mmpy and the lowest corrosion rate was obtained for wall nails with an average corrosion rate of 0.02 mmpy. The largest difference in nail weight after soaking was for the umbrella nail at 0.48 grams, while the smallest difference in nail weight was for the wall nail at 0.11 grams.